2009
DOI: 10.1111/j.1467-9930.2009.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Decentralization: Environmental Impact Assessment and Water Pollution Control in Indonesia

Abstract: After having been one of the most centralized states in the world for more than thirty years, in 2001 Indonesia introduced a sweeping program of decentralization with important consequences for the management of the industrial sector. This article explores whether the decentralization process has led to substantial changes in Environmental Impact Assessment (EIA) and enforcement of water pollution law. Its main findings are that the general division of authority in both fields has become less fragmented and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…EA is an external configuration which is incorporated in the annual report as Indonesian accounting regulation does not regulate specific standards. Bedner (2010) suggested that the authority is divided across various government levels to give a clear influence on the performance of environmental control; hence, the processes of standard setting, and monitoring and imposing sanctions to protect the environment are in the environmental regulator.…”
Section: Regulator and Managerial Rolesmentioning
confidence: 99%
“…EA is an external configuration which is incorporated in the annual report as Indonesian accounting regulation does not regulate specific standards. Bedner (2010) suggested that the authority is divided across various government levels to give a clear influence on the performance of environmental control; hence, the processes of standard setting, and monitoring and imposing sanctions to protect the environment are in the environmental regulator.…”
Section: Regulator and Managerial Rolesmentioning
confidence: 99%
“…Adriaan Bedner's article in this issue (2010) examines the relationship between large governmental change and regulatory law implementation and enforcement. Bedner's focus is on how Indonesian decentralization reforms, initiated in 1999, affected the implementation of legal requirements for environmental impact assessments and the enforcement of pollution law.…”
Section: Enforcement Variation and Its Institutional Contextmentioning
confidence: 99%
“…Regulatory reforms in Indonesia in the 1990s and 2000s involved a turn towards using alternative regulatory instruments as well as decentralization (cf. Bedner 2010). McCarthy and Zen show that the supposed gains in regulatory responsiveness associated with decentralization have been hobbled by jurisdictional coordination problems as well as resource and capacity constraints at the local level.…”
Section: Alternative Regulatory Instruments and Enforcementmentioning
confidence: 99%
“…Some commentators claim that governance standards have worsened, but others point to improvements in health and education in some regions. See Pratikno (2005); Kristiansen & Santoso (2006); Ahmad et al (2005); Arnold (2009); Hill (2014); Lieberman & Marzoeki (2002); Barr (2006); Lewis & Pattinasarany (2009); Bedner (2010).…”
mentioning
confidence: 99%